Size effect and the Common Variation in stock returns: Evidence from the Indian Stock Market - Zhang, Zhuoqi (2012)
This paper examines the widely known size effect in the Indian stock market and examines the explanatory power of the risk factors which explain the common variation in stock returns using the Fama and French three-factor model and the CAPM. Unlike recent evidence of a strong size effect in the Indian stock market, I detect a slight reversal of the size effect. Small stocks do seem to beat big stocks in terms of average monthly return. The market risk has the most explanatory power for the variation in stock returns. Size has the strongest explanatory power in explaining the returns on small stocks. Book-to-market ratio is strong in explaining returns on stocks with high book-to-market ratio, but its explanatory power is not as strong as that of the market.